The Relationship Of Knowledge And Attitude Of Mother’s Breasfeeding With Exclusive Giving (JPK : Jurnal Proteksi Kesehatan, 2020)
Breast milk (ASI) is the only food that is the best for babies, because it has themost complete nutritionalcomposition for baby’s growth and development.Methode: this research is analytic using cross sectional approach. The samplingtechnique is by simple random sampling. Data analysis was performed using theChi-Square test at a significance level of p